Situation report on Nepal’s agrifood systems: December 2023 - Palikhe, A.; Gupta, S.; Maharjan, N.K.; Adhikari, M.; Kumar, A.; Minot, Nicholas; Koirala, P.; Koirala, Pankaj (CSISA, 2023)
In November 2023, the year-on-year Consumer Price Inflation (CPI) in Nepal stood at 5.4 percent. Compared to September-October, a modest decline of 0.22 percent was observed compared to the CPI in October-November. Most food and beverages experienced a decline in prices in October-November compared to the previous month, with the highest decline in vegetables (3.6 percent). However, published reports suggest that the prices of potato1 and onion2 have significantly increased. While the decline in the prices of most vegetables can be attributed to increased seasonal production, benefiting poor consumers in both rural and urban areas, the increases in the prices of potato and onion appear to be affected by untimely rainfall and India's export new restrictions, combined with Nepal's imposition of Value Added Tax (VAT). Higher potato and onion prices will negatively affect consumers’ food baskets.